2012
DOI: 10.1093/scan/nss004
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional mindfulness and the attenuation of neural responses to emotional stimuli

Abstract: Considerable research has disclosed how cognitive reappraisals and the modulation of emotional responses promote successful emotion regulation. Less research has examined how the early processing of emotion-relevant stimuli may create divergent emotional response consequences. Mindfulness--a receptive, non-evaluative form of attention--is theorized to foster emotion regulation, and the present study examined whether individual differences in mindfulness would modulate neural responses associated with the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
197
4
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(226 citation statements)
references
References 40 publications
22
197
4
3
Order By: Relevance
“…Brown, Goodman, and Inzlicht (2013) suggest that dispositional mindfulness plays a role in moderating early affective processing. In Study 3 we found a positive correlation between mindfulness and NFC and a negative correlation between mindfulness and NFA.…”
Section: Discussionmentioning
confidence: 99%
“…Brown, Goodman, and Inzlicht (2013) suggest that dispositional mindfulness plays a role in moderating early affective processing. In Study 3 we found a positive correlation between mindfulness and NFC and a negative correlation between mindfulness and NFA.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness has been operationalized using various methods, with mindfulness variously being measured as a disposition (Brown, Goodman, & Inzlicht, 2013;Creswell, Way, Eisenberger, & Lieberman, 2007), as an acquired skill (Farb et al, 2007;Jha et al, 2007;, or as a psychological state promoted by brief, targeted inductions (Erisman & Roemer, 2010;Larson et al, 2013). One strength of the present study was that our manipulations uniquely allowed us to differentiate between the influences of different forms of present-moment awareness more easily than could be managed by correlational approaches.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In particular, this physiological dysregulation may serve as an indicator of a reduced capacity to monitor and therefore predict, one's environment. According to Brown and Ryan (2003), individuals naturally exhibit differences in the propensity to be engaged with, and responsive to, their surroundings; this personal disposition is referred to as mindfulness (Brown, Goodman, & Inzlicht, 2012), and it has been associated with increased sympathetic arousal (Lumma, Kok, & Singer, 2015), as well as greater self‐regulation (Short, Mazmanian, Oinonen, & Mushquash, 2016). Notably, Krzeczkowski, Robb, and Good (2017) found that individuals with a history of concussion who endorsed greater trait mindfulness presented with fewer postconcussive symptoms.…”
Section: Discussionmentioning
confidence: 99%